The future role of mitochondrial drugs in vascularized composite allotransplantation: A short review - Leonard Knoedler; Daniel H. Mendelsohn; Loïc Van Dieren; Thomas Schaschinger; Cosima C. Hoch; Max Heiland; Jasper Iske; Felix J. Klimitz; Maxime Jeljeli; Korkut Uygun; Curtis L. Cetrulo; Alexandre G. Lellouch (Cell Transplantation)
Vascularized composite allotransplantation (VCA) has emerged as an innovative strategy to restore form and function in patients with severe tissue defects involving anatomical regions such as the face, hand, and abdominal wall. Composite allografts are composed of diverse tissues, including skin, muscle, bone, vasculature, nerves, and mucosal surfaces, posing unique challenges in immunological management. Clinical outcomes following VCA surgeries have been encouraging; however, a comprehensive understanding of the underlying cellular interactions and molecular pathways is still predominantly derived from studies in solid organ transplantation (SOT). Recent advances in SOT have identified mitochondria as crucial therapeutic targets capable of mediating transplant rejection, mitigating ischemia-reperfusion injury (IRI), and enhancing graft longevity. Nevertheless, the explicit role and potential therapeutic applications of mitochondria within VCA remain largely unexplored. This review aims to critically examine and elucidate the significance of mitochondria in overcoming the current limitations encountered in VCA surgery. A deeper insight into mitochondrial biology could hypothetically provide clinicians and researchers with novel, targeted therapeutic strategies to improve clinical outcomes in VCA; however, these approaches require further validation in preclinical models.